KEANEKARAGAMAN GENETIK RAMIN (Gonystylus bancanus Miq. Kurz) DI CAGAR BIOSFER GIAM SIAK KECIL-BUKIT BATU KABUPATEN BENGKALIS PROVINSI RIAU BERDASARKAN POLA PITA ISOZIM - Meilian Syafitri; Ninik Nihayatul Wahibah; Siti Fatonah (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Ramin is timber plant with high demand in furniture industries because it has good woodand fiber texture. The high selling prices and market demand has led to increase illegallogging, consequently ramin population will be endangered. Therefore, it is necessary tostudy the genetic diversity as one of the conservation effort of ramin using biochemicalmarkers. This study was aimed to analyze the genetic diversity of ramin (Gonystylusbancanus Miq. Kurz) in Giam Siak Kecil-Bukit Batu Bengkalis biosphere reserves using anisozymes technique. Isozyme analysis was performed using the horizontal model of starchgel electrophoresis. A total of 50 individual ramins were used for analyzing the isozymebanding patterns using one enzyme namely peroxidase (PER). The result showed clearbanding patterns. PER enzyme produced twelve banding patterns and migrated to theanode (positive) and cathode (negative) poles. SAHN clustering analysis using UPGMAmethod showed that all of the individuals of ramin were clustered with the similaritycoefficient of 38% and separated into two groups (I and II). All of the members of firstcluster were grouped with the similarity coefficient 61%, while the second cluster memberswere grouped with similarity coefficient 55%. This data indicated that the genetic diversityof ramin in biosphere reserves Giam Siak Kecil-Bukit Batu Bengkalis Regency of RiauProvince was quite high.